Folate intakes from diet and supplements may place certain Canadians at risk for folic acid toxicity. Issue 7 (9th September 2016) - Mudryj, Adriana N.; de Groh, Margaret; Aukema, Harold M.; Yu, Nancy
Abstract: To examine the prevalence of folate inadequacy and toxicity based on usual intakes from food and supplements, as well as biomarkers of folate, secondary data analyses were performed using cross-sectional, nationally representative data from the Canadian Community Health Survey, Cycle 2.2 ( n 32 776), as well as biomarker data from the Canadian Health Measures Survey, Cycles 1, 2 and 3 ( n 15 754). On the basis of unfortified food sources, Canadians would struggle to consume adequate amounts of folate. When folate intakes from all food sources were considered, the overall prevalence of folate inadequacy was low across all age/sex groups, with the exception of females >70 years. However, >10 % of supplement users were above the tolerable upper intake level, increasing to almost 18 % when overage factors were accounted for. In addition, between 20 and 52 % of supplement users had elevated erythrocyte folate concentrations, depending on the cut-off used. Results from this study suggest that insufficient dietary intakes of folate in Canadians have been ameliorated because of the fortification policy, although folate inadequacy still exists across all age groups. However, supplement users appear to be at an increased risk of folic acid (FA) overconsumption as well as elevated erythrocyte folate. As such, the general population should be informed of the potential risks of FA overconsumption resulting from supplement use. This study suggests a need for more careful assessment of the risks and benefits of food fortification, particularly fortification above mandated levels, and FA supplement use in the general population.